Kajian Dakwah Kultural Pondok Pesantren Tahfidz Kiai Marogan Palembang dalam Mengembangkan Masyarakat Islam - Muslimin Muslimin (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2020)
Cultural Da'wah is a da'wah activity that can be carried out using scientific approaches, customs, arts, and other cultural elements. Cultural Da'wah can also be used to understand the religious phenomena found at the empirical and practical level. Religious experience in the community is processed by adherents from religious sources, namely through reasoning and interpretation of religious texts. Therefore, the purpose of this study is to propose and explain the cultural da'wah of the tahfidz Islamic boarding school in Kiai Marogan, Palembang. This research is related to the cultural propaganda of Tahfidz Kiai Marogan Islamic Boarding School including the establishment of Tahfidz Kiai Marogan Kindergarten, the establishment of Tahfidz Kiai Marogan Middle School, Tahfidz Teacher Quarantine Program for Orphan Independence, Addition of the Location of the Tahfidz Kiai Marogan Islamic Boarding School in Plaju.